Properties of Easy Concrete from Waste Porosity Aggregates (Recycled Aggregate) - Kh., Kuldashev; A., Qo’ziboyev; Sh., Esonov (European Journal of Life Safety and Stability (2660-9630), 2022)
The purpose of this study was to develop porous concrete with acceptable permeability and strength using recycled aggregate from waste porosity aggregates. The optimum mix proportions were employed to prepare easy concretes using normal and recycled aggregates. Four different mixes were prepared and tested, which po was used as a coarse aggregate from mass of aggregate 25, 40 and 75%. in 6 consists. Investigated and test results showed, that incorporation coarse aggregate into a mix increase flexural straight to 150% and 155%